Metabolite Profile, Ruminal Methane Reduction, and Microbiome Modulating Potential of Seeds of Pharbitis nil - Bharanidharan, Rajaraman; Thirugnanasambantham, Krishnaraj; Ibidhi, Ridha; Baik, Myunggi; Kim, Tae Hoon; Lee, Yookyung; Kim, Kyoung Hoon (Frontiers in Microbiology, 2022)
We identified metabolites in the seeds of Pharbitis nil (PA) and evaluated their effects on rumen methanogenesis, fiber digestibility, and the rumen microbiome in vitro and in sacco. Four rumen-cannulated Holstein steers (mean body weight 507 ± 32 kg) were used as inoculum donor for in vitro trial and live continuous culture system for in sacco trial. PA was tested in vitro at doses ranging from 4.5 – 45.2% dry matter (DM) substrate. The in sacco trial was divided into three phases: a control phase of 10 days without nylon bags containing PA in the rumen, a treatment phase of 11 days in which nylon bags containing PA (180 g) were placed in the rumen, and a recovery phase of 10 days after removing the PA-containing bags from the rumen. Rumen headspace gas and rumen fluid samples were collected directly from the rumen. PA is enriched in polyunsaturated fatty acids dominated by linoleic acid (C18:2) and flavonoids such as chlorogenate, quercetin, quercetin-3-O-glucoside, and quinic acid derivatives. PA decreased (p < 0.001) methane (CH4) production linearly in vitro with a reduction of 24% at doses as low as 4.5% DM substrate. A quadratic increase (p = 0.078) in neutral detergent fiber digestibility was also noted, demonstrating that doses < 9% DM were optimal for simultaneously enhancing digestibility and CH4 reduction. In sacco, a 50% decrease (p = 0.087) in CH4 coupled with an increase in propionate suggested increased biohydrogenation in the treatment phase. A decrease (p < 0.005) in ruminal ammonia nitrogen (NH3-N) was also noted with PA in the rumen. Analysis of the rumen microbiome revealed a decrease (p < 0.001) in the Bacteroidetes-to-Firmicutes ratio, suggesting PA to have antiprotozoal potential. At the genus level, a 78% decrease in Prevotella spp. and a moderate increase in fibrolytic Ruminococcus spp. were noted in the treatment phase. In silico binding of PA metabolites to cyclic GMP-dependent protein kinase of Entodinium caudatum supported the antiprotozoal effect of PA. Overall, based on its high nutrient value and antiprotozoal activity, PA could replace the ionophores used for CH4 and nitrogen abatement in the livestock industry.